An integrated electrochemical process to convert lignin to value-added products under mild conditions. Issue 18 (14th June 2016) - Stiefel, Serafin; Schmitz, Annika; Peters, Jens; Di Marino, Davide; Wessling, Matthias
Abstract : The controlled depolymerization of lignin is a promising approach for the generation of value-added compounds from biomass. Abstract : The controlled depolymerization of lignin is a promising approach for the generation of value-added compounds from biomass. And even though many different technologies to this end have been developed in the past, most of them require elevated temperatures and pressures to realize the depolymerization. In contrast, the electrochemical depolymerization of lignin can be achieved at ambient pressure and room temperature. However, as electrochemical processes are predominantly surface-catalyzed, the influence of the electrode structure plays a major role with regard to the process effectivity. In addition, the unselective mechanism of the electrochemical process reduces product yield by overoxidizing products. We report the use of 3D-structured electrode materials for the electrochemical depolymerization of lignin with a subsequent membrane filtration in order to increase product yield. The complete depolymerization of lignin at room temperature and ambient pressure to monomeric products could be achieved in less than four hours, with the successful continuous separation of monomers and residual lignin.